Risk attitude among entrepreneurs venturing into family businesses of small and medium enterprises (SME) / Siti Nurul Aini Mohd Rodzi, Mursyida Mahshar and Siti Nazirah Omar - Mohd Rodzi, Siti Nurul Aini; Mahshar, Mursyda; Omar, Siti Nazirah (Universiti Teknologi MARA, Kedah, 2024)
Most small and medium enterprises (SMEs) in Malaysia engage in activities related to manufacturing, trading, and retailing, collectively contributing approximately RM521.7 billion to the country's gross domestic product. Notably, a significant 80% of businesses in Malaysia, including those under the SME category, are family-owned (PricewaterhouseCoopers, 2018). Given that family-owned small and medium enterprises (SMEs) constitute a significant segment of the corporate landscape in Malaysia, the country's economy is heavily reliant on the entrepreneurial competence of these family-run businesses (Yew, 2021). Typically, a family-run business is owned and operated by a single-family lineage, and its sustained success hinges on effectively managing the risks associated with succession planning and maintaining control of equity (Saleh, 2020). According to the Family Business Survey Report 2018 by the Associated Chinese Chambers of Commerce and Industry of Malaysia (ACCCIM), only 23% of Malaysian family-owned businesses are ready with a succession plan in place (The Associated Chinese Chambers of Commerce and Industry of Malaysia (ACCCIM), 2019)